(untitled) (Revista científica Olimpia, 2024)
The present work aims to prepare a methodological alternative to perfect the combined training of special troops cadets from the optimal relationships of various physical capabilities, skills and didactic components, in the process of instruction of the physical preparation of the Cadets of special troops during the stages of special preparation and maximum requirement of the school Interarmas "General José Maceo. The research methods used were analysis - synthesis, induction - deduction and systemic-structural - functional, as well as scientific observation and documentary review. As a result of the study carried out in the programs and methodological indications it was found that the correct combination of the aforementioned elements is not taken into account, being able to cause the non-harmony and profitability of the efforts to each capacity, in addition to producing negative transfers. The importance of this research is that teachers are provided with a different option to improve the quality of the results and expectation in the classes of special troops cadets and thus achieve compliance with the proposed objectives.